Risk prediction in patients with classical Low-flow, low-gradient aortic stenosis undergoing TAVI. (14th October 2021) - Ludwig, S; Gruhl, L; Gossling, A; Seiffert, M; Westermann, D; Sinning, J M; Sugiura, A; Adam, M; Mauri, V; Frank, D; Seoudy, H; Rudolph, T K; et al.
Abstract: Background: Patients with classical low-flow, low-gradient aortic stenosis (LFLG AS) undergoing transcatheter aortic valve implantation (TAVI) are known to suffer from poor prognosis. Risk prediction is difficult and predictors of outcome are scarce in this complex patient subset. Purpose: This study aimed to develop a simple score system for risk prediction in patients with classical LFLG AS scheduled for TAVI including baseline clinical, echocardiographic and computed tomography (CT) parameters. Methods: Among 9, 150 patients undergoing TAVI (2008–2019) at five German centers, patients with classical LFLG AS were screened for availability of sufficient CT data for aortic valve calcification (AVC) quantification. Score variables were defined as all variables included into the best performing multivariable regression model. Score performance was assessed by Kaplan-Meier analysis for the endpoint of 1-year all-cause as well as c-index calculation. Results: A total of 718 patients were included into the study. Predictors of all-cause mortality were male sex (HR 1.27 [0.98, 1.65], p=0.068), chronic obstructive pulmonary disease (HR 1.59 [1.21, 2.08], p<0.001), atrial fibrillation (HR 1.33 [1.03, 1.70], p=0.026), stroke volume index (HR 0.96 [0.94, 0.98], p<0.001), non-transfemoral access (HR 1.44 [1.09, 1.91], p=0.011), pulmonary hypertension (HR 1.58 [1.20, 2.08], p=0.0012) and low AVC density (HR 1.49 [1.16, 1.90], p=0.0016). A score system was developed ranging from 0 points to 11 points. Kaplan-Meier analysis for low (0–2 points), moderate (3–6 points) and high score (>6 points) demonstrated 1-year mortality rates of 20.9%, 28.9% and 64.3% (p<0.001), respectively. C-index for prediction of 1-year mortality was 0.69 (95%-CI 0.65–0.84). The RELiEF TAVI score outperformed classical risk prediction models like the logistic euroSCORE (c-index 0.60 [95%-CI 0.51–0.72], p=0.013), the EuroSCORE II (c-index 0.57 [95%-CI 0.45–0.70], p=0.039) and the STS PROM (c-index 0.60 [0.48–0.70], p=0.035). Conclusions: The RELiEF TAVI score is based on simple clinical, echocardiographic and CT parameters and might serve as a helpful tool for risk prediction in the vulnerable subset of patients with classical LFLG AS scheduled for TAVI. Funding Acknowledgement: Type of funding sources: None.